Mutation analysis of candidate genes SCN1B, KCND3 and ANK2 in patients with clinical diagnosis of Long QT syndrome - Raudenská, Martina; Bittnerová, Alexandra; Novotný, Tomáš; Floriánová, Alena; Chroust, Karel; Gaillyová, Renata; Semrád, Bořivoj; Kadlecová, Jitka; Šišáková, Martina; Toman, Ondřej; Špinar, Jindřich (Physiological research, 2008)
The long QT syndrome (LQTS) is a monogenic disorder characterized by prolongation of the QT interval on electrocardiogram and syncope or sudden death caused by polymorphic ventricular tachycardia (torsades de pointes). In general, mutations in cardiac ion channel genes (KCNQ1, KCNH2, SCN5A, KCNE1, KCNE2) have been identified as a cause for LQTS. About 50-60 % of LQTS patients have an identifiable LQTS causing mutation in one of mentioned genes. In a group of 12 LQTS patients with no identified mutations in these genes we have tested a hypothesis that other candidate genes could be involved in LQTS pathophysiology. SCN1B and KCND3 genes encode ion channel proteins, ANK2 gene encodes cytoskeletal protein interacting with ion channels. To screen coding regions of genes SCN1B, KCND3, and 10 exons of ANK2 following methods were used: PCR, SSCP, and DNA sequencing. Five polymorphisms were found in screened candidate genes, 2 polymorphisms in KCND3 and 3 in SCN1B. None of found polymorphisms has coding effect nor is located close to splice sites or has any similarity to known splicing enhancer motifs. Polymorphism G246T in SCN1B is a novel one. No mutation directly causing LQTS was found. Molecular mechanism of LQTS genesis in these patients remains unclear.
Keywords: Candidate genes; financování organizované; mužské pohlaví; genetická predispozice k nemoci; Male; Financing, Organized; KCND3; Long QT syndrome; Long QT Syndrome; Ankyrins; ankyriny; Female; Humans; Shal Potassium Channels; Genetic Predisposition to Disease; Polymorphism, Single Nucleotide; lidé; DNA Mutational Analysis; Sodium Channels; Middle Aged; ženské pohlaví; lidé středního věku; jednonukleotidový polymorfismus; sodíkové kanály; mladiství; Young Adult; syndrom dlouhého QT; Adolescent; mutace; mladý dospělý; ANK2; dospělí; Mutation; Adult; SCN1B; draslíkové kanály Shal; mutační analýza DNA